Lean triz : how to dramatically reduce product-development costs with this innovative problem-solving tool - Harrington, H. James; Taylor and Francis (Boca Raton, FL : Productivity Press, an imprint of Taylor and Francis, 2017)
Lean TRIZ is a new workshop-based process that brings together teams to focus on specific processes, evolutionary product designs, and improvement opportunities. It combines the insight of TRIZ with the simplicity of Value Engineering, EXPRESS, or FAST methodologies. TRIZ is the most advanced problem solving tool available. By combining TRIZ's simplest concepts with those in the EXPRESS methodology (used by Ford and Ernst & Young), it is feasible to apply this new methodology to new concepts that are not traditionally applicable to the TRIZ methodology. This combination is guaranteed to greatly improve the quality and breakthrough results of a team that works on the problem within two days.
chapter 1 Introduction to n LTM -- chapter 2 Five Special LTM n Methodologies -- chapter 3 Starting an LTM n Program -- chapter 4 Phase I?Identifying n the Opportunities -- chapter 5 Phase II?Preparing for n the Workshop -- chapter 6 Phase III?Conducting n the Workshop -- chapter 7 Phase n IV?Implementing the Change (Recommendations) -- chapter 8 Phase V?Measuring n Results and Rewards/Recognition.
Keywords: Engineering -- Methodology; Inventions; Lean manufacturing; Product design -- Methodology; Teams in the workplace; TRIZ theory